2020
DOI: 10.1002/ajmg.c.31857
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imbalances in craniofacial microsomia

Abstract: The aim of this study was to perform 22q11.2 deletion screening and chromosomal microarray analysis (CMA) in individuals clinically diagnosed with craniofacial microsomia (CFM) and review previously published cases of CFM with genomic imbalances. It included 54 individuals who were evaluated by a clinical geneticist. Copy number variants (CNVs) in the 22q11.2 region were investigated by multiplex ligation-dependent probe amplification (MLPA) for all individuals. The CMA was performed only for individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…43 Moreover, an OAVS patient carrying a chromosome 9p22.1 duplication mapping close to the deletion of our patient has been recently described. 35 Hence, it is likely that the complex phenotype of our patient derives from co-occurring CNVs, where del (9p22), contributes to craniofacial features, and del (15q26.2q26.3) is causally associated with the other features (i.e., CHD, IUGR, and DD). The last OAVS subject with CNV and septal defect had a small duplication on chromosome 8q23.3 within CSMD3, a giant gene with unknown function, expressed mainly in brain and testis.…”
Section: Discussionmentioning
confidence: 94%
“…43 Moreover, an OAVS patient carrying a chromosome 9p22.1 duplication mapping close to the deletion of our patient has been recently described. 35 Hence, it is likely that the complex phenotype of our patient derives from co-occurring CNVs, where del (9p22), contributes to craniofacial features, and del (15q26.2q26.3) is causally associated with the other features (i.e., CHD, IUGR, and DD). The last OAVS subject with CNV and septal defect had a small duplication on chromosome 8q23.3 within CSMD3, a giant gene with unknown function, expressed mainly in brain and testis.…”
Section: Discussionmentioning
confidence: 94%
“…Only few CNVs appeared to be recurrent. Interestingly, several studies reported 22q11.2 deletions or duplications in patients with OAVS phenotype 26–36. Some of these CNV have different boundaries compared with those found in DiGeorge syndrome and complex rearrangements were rarely described.…”
Section: Aetiologiesmentioning
confidence: 99%
“…Goldenhar syndrome is characterized by facial asymmetry and pronounced facial defects, like microtia or anotia, benign ocular growths, and spinal abnormalities [ 37 , 38 ]. Goldenhar syndrome has been associated with 22q11.2 deletion syndrome [ 39 , 40 ]. It is interesting that our patient has a deletion in 22q11.2 LCR A whereas the reported cases harbor proximal, central, and distal deletions [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goldenhar syndrome has been associated with 22q11.2 deletion syndrome [ 39 , 40 ]. It is interesting that our patient has a deletion in 22q11.2 LCR A whereas the reported cases harbor proximal, central, and distal deletions [ 39 , 40 ]. Goldenhar syndrome shows significant locus heterogeneity and has been associated with copy number variations (CNVs) at multiple chromosome regions including Xp22.33p22.31, 1p22.2p31.3, 2p11.2, 2p12, 2q11, 3q29, 4p16.3p15.33, 5p15, 5q22, 8q13.3, 9p22.1, 10q26.2q26.3, 12p13.33, 13q34, 14q23.1, 14q31.1q31.3, 15q24, 16p13.3, 17q11.2, 22q11.1, 22q11.1q11.21, and 22q11.2 [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%